Factors affecting green office building value in Kuala Lumpur / Nur Eamyra Hisham - Hisham, Nur Eamyra (2023)
In Malaysia, there is currently a noticeable increase in the number of green structures, particularly green offices. This trend is driven by the perception that green buildings are more valuable than conventional buildings, with higher rental rates being seen in Kuala Lumpur in particular. However, there is a significant research gap regarding the specific factors that have a significant influence on the value of green office buildings. Therefore, this study aims to close this gap by identifying the factors that impact the value of green office buildings in Kuala Lumpur and investigating the main factors that influence the value of green office buildings in Kuala Lumpur. Three participants who are registered valuers and assistant valuer from Ian Scott International (M) Sdn Bhd, IM Global Property Consultants Sdn Bhd, and Intra Harta Consultants Sdn Bhd were subjected to semi-structured face-to-face and online interviews. All of the participant are the valuer that working in Kuala Lumpur, these valuers being chosen as the participant because they have an experience in valuing green office buildings specific in Kuala Lumpur and they have wide knowledge regarding the market condition in Kuala Lumpur. The selection of the green office building in Kuala Lumpur was based on careful consideration of various factors.